2016
DOI: 10.1155/2016/3727689
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in Homeless People: Clinical Outcomes and Cost Analysis in a Single Institute

Abstract: Introduction. To characterize the demographic and clinical features, outcomes, and treatment costs of lung cancer in homeless people. Methods. Medical records of 22 homeless patients with lung cancer at Seoul National University Boramae Medical Center in Seoul, South Korea, were retrospectively analyzed. Results. All patients were men (median age, 62 years). Most patients (78%) had advanced disease (stage IIIB, n = 2; stage IV, n = 15). Seven died during initial hospitalization (median survival, 1.5 months). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The origins of homelessness are multi-faceted, both on individual and structural levels, for example the ageing population (van Dongen et al, 2019;Fazel et al, 2014), changes in the housing market with shifts in family structures (NBHW, 2017), migration (EU, 2013), rising costs for housing (NBHW, 2017) and poor health (van Dongen et al, 2019;Fazel et al, 2014;Lewer et al, 2019). A growing body of research concludes that homelessness is associated with heavy costs for society with regards to public health, social and legal services (Basu, Kee, Buchanan, & Sadowski, 2012;Fuehrlein et al, 2015;Larimer et al, 2009;Mitchell, Leon, Byrne, Lin, & Bharel, 2017;Suh et al, 2016). However, the samples in the studies often consist of highly selected subgroups, like individuals with a certain specific diagnosis or demographic criteria like ethnicity or gender orientation, making comparisons and inferences challenging.…”
mentioning
confidence: 99%
“…The origins of homelessness are multi-faceted, both on individual and structural levels, for example the ageing population (van Dongen et al, 2019;Fazel et al, 2014), changes in the housing market with shifts in family structures (NBHW, 2017), migration (EU, 2013), rising costs for housing (NBHW, 2017) and poor health (van Dongen et al, 2019;Fazel et al, 2014;Lewer et al, 2019). A growing body of research concludes that homelessness is associated with heavy costs for society with regards to public health, social and legal services (Basu, Kee, Buchanan, & Sadowski, 2012;Fuehrlein et al, 2015;Larimer et al, 2009;Mitchell, Leon, Byrne, Lin, & Bharel, 2017;Suh et al, 2016). However, the samples in the studies often consist of highly selected subgroups, like individuals with a certain specific diagnosis or demographic criteria like ethnicity or gender orientation, making comparisons and inferences challenging.…”
mentioning
confidence: 99%
“…16,17 Minimal research has been done to describe the association between cancer health disparities among homeless populations and health literacy. 18,19 A scoping review of the literature was conducted to examine and summarize what is known about homelessness, cancer and health literacy.…”
mentioning
confidence: 99%
“…increased distress may compound already dire outcomes for homeless patients with cancer. Studies in this population are scarce, but Suh et al27 showed that homeless patients with lung cancer present late, have an overall survival of less than 3 months, and less than one quarter received appropriate treatment for their cancer or related symptoms. Therefore, identifying and addressing concerns about homelessness in cancer patients is of utmost importance.Telephone follow-up of patients reporting elevated distress at baseline revealed the practical difficulty of reaching our patient population.…”
mentioning
confidence: 99%